Employability and the rise of the no-wage economy: resistance to unpaid work in the United Kingdom - Weghmann, Vera (2018)
Employability has become a new buzzword of the 21st century. It advocates that to keep oneself attractive - through lifelong learning and the continuous acquisition of skills - protects oneself from the vulnerabilities of the labour market. The purpose of this PhD project is twofold: First, I investigate in what ways the employability agenda recreates neoliberal hegemony. Second, I analyse through what type of collective agency people contest the concept of employability. It is a comparative project of two main employability sectors, namely welfare to work programmes and higher education. In particular, I elaborate on the link between employability and the rise of unpaid labour in form of work-experiences. In line with neo-Gramscian theory and my critique of it this PhD research looks at the material structures, institutions and ideology which have shaped the political economy of employability through processes of class contestation. Participatory Action Research methodology is used to provide insights into the formations, dynamics, and outcomes of the main social forces resisting employability outside of established trade unions. This PhD, thereby, feeds into broader discussions on the decline and future of trade unionism and new ways of organising around work, which go beyond the workplace and might demand new workers institutions as well as a greater engagement with other actors in the community.